Sistem Informasi Manajemen Persediaan Bahan Baku Dengan Menggunakan Metode Economic Order Quantity (EOQ) Dan Just In Time (JIT) Berbasis Web - Rofi’ul Azis, Moh.; Mashuri, Chamdan; Faizah, Arbiati (Inovate, 2020)
Raw material inventory management is very important to be carried out by companies in the process of production activities. The importance of inventory management is also used to address the causes of stock outages and waste of company funding sources. So that further analysis is required by using methods related to inventory management. In addition to further analysis, a computerized system is also needed that can manage raw material inventory management so that it can process automatically and is judged to be more effective. The method used in the study uses the Economic Order Quantity (EOQ) and Just-in-Time (JIT) methods. Both methods were chosen because they are more suitable to be applied in a company problem, especially in the matter of raw material inventory management. Of the two methods will be carried out a comparison process to find out which method is more effective when used. The results of this study are computerized systems used to determine raw material inventories by the EOQ and JIT methods. From the results of the calculation of the two methods, the final result of the JIT method is Rp. 3.654.495, while the EOQ method obtained a value of Rp. 6.603.181. By looking at the values generated by the two methods, it can be concluded that the JIT method is more efficient than the EOQ method. Keywords: EOQ, JIT, Raw material inventory